Matroids, some vector space of graphs and some generator subgraphs of some graphs - Eslamian, Sara (Animo Repository, 2016)
In this paper we show that the set of all subsets of a symmetric digraph forms a vector space over F3 = f{u100000}1 0 1g. Also we give some characterization for the generator subgraphs of pth power of cycles denoted by Cpn , where n > 3. In addition, we show some generator subgraphs of tadpole and double graphs. We also de ne the even vertex space and use this concept to determine the generator subgraphs of the generalized Petersen graph. The generator subgraphs of some operations on graphs are also established. Lastly, the relation between generator subgraphs and cycle matroid was investigated.